Digital Cynicism and the Eroding Social Contract: A Longitudinal Structural Equation Modeling Analysis of Youth Political Trust and State-Led Counter-Narratives in Indonesia (2019–2025) - Aman Suparman; Mary-Jane Wood; Omar Alieva; Henny Kesuma (Open Access Indonesia Journal of Social Sciences, 2025)
The 2019 #ReformasiDikorupsi movement served as a watershed moment for Indonesian youth activism. However, the subsequent six years have witnessed a transition from active mobilization to a state of pervasive digital cynicism. This study investigates the longitudinal impact of state-led counter-narratives on the political trust of Gen Z and Millennials. Utilizing a longitudinal panel design, we analyzed a cohort of 2,400 respondents across 34 Indonesian provinces from 2019 to 2025. We employed Structural Equation Modeling to test the mediating role of digital cynicism between exposure to state-led counter-narratives and institutional trust. Findings indicate that while state counter-narratives initially neutralized protest sentiment, they triggered a significant long-term surge in digital cynicism (beta = 0.48, p < 0.001). This cynicism acts as a primary barrier to formal political engagement, leading to a trust deficit that has deepened by 32 percent since 2019. The study concludes that state efforts to manage online dissent through top-down narratives have paradoxically undermined democratic legitimacy among the youth. The shift from #ReformasiDikorupsi to digital cynicism represents a fundamental decoupling of the youth from the state’s democratic promises.